KELIMPAHAN POPULASI DAN TINGKAT EKSPLOITASI IKAN TERUBUK (Tenualosa macrura) DI PERAIRAN BENGKALIS, RIAU - Efizon, Deni; Djunaedi, Otong Suhara; Dhahiyat, Yayat; Koswara, Bachrulhajat (Berkala Perikanan Terubuk, 2012)
Fish terubuk (Tenualosa macrura) isone of thefive species terubukspecies in the world. This fish is a fish Bengkalis community pride,but thepopulation has fallensignificantly comparedto previousyears. Thisstudy aimed to examine the various aspects in view of abundance and exploitationrates of fish terubuk at this time.From the research results obtained in the waters of fish terubukBengkalis contained in two age groups of "pale" and "terubuk" with the rangeof 15-20 cm length and pias for the range of 21-43 cm length for terubuk.Looking at the various parameter of the population, on fish stocksterubuk currentlyexperiencing overfishing. Thisisevidentfrom thevaluesof population parameters suchas growthrate (K)of 0.62 andamaximum standard length (L ∞) = 46.62 cm; arrest mortality rate(F) of 1.853 isgreater than the rate of natural mortality (M ) of 1.22.Alleged amount of fishstocks terubuk today in the form of biomassper recruit an average of (B / R)of 0.80 kg per recruit in the catch perrecruit (Y / R) of 0.45. With the levelof exploitation that has exceededthe maximum sustainable (MSY), which isreflected in the value of Exploitation Rate (E) in excess of 0.5 is 0.603.